Hypoxic-conditioned cardiosphere-derived cell sheet transplantation for chronic myocardial infarction. (24th April 2019) - Fujita, Akira; Ueno, Koji; Saito, Toshiro; Yanagihara, Masashi; Kurazumi, Hiroshi; Suzuki, Ryo; Mikamo, Akihito; Hamano, Kimikazu
Abstract: OBJECTIVES: Cell therapy provides a suitable environment for regeneration through paracrine effects such as secretion of growth factors. Cardiosphere-derived cells (CDCs) have a high capacity for growth factor secretion and are an attractive target for clinical applications. In particular, a cell sheet technique was reported to have clinical advantages by covering a specific region. Here, we examined the effect of the hypoxic-conditioned (HC) autologous CDC sheet therapy on a rabbit chronic myocardial infarction model. METHODS: CDC sheet function was assessed by the enzyme-linked immunosorbent assay and quantified by polymerase chain reaction in vitro (days 1–3 of conditioning). The rabbit chronic myocardial infarction model was established by left coronary ligation. Autologous CDCs were isolated from the left atrial specimen; CDC sheets with or without 2-day HC were transplanted onto the infarcted hearts at 4 weeks. The cardiac function was assessed by an echocardiography at 0, 4 and 8 weeks. A histological analysis of the host hearts was performed by tomato lectin staining at 8 weeks. RESULTS: The optimal HC duration was 48 h. HC significantly increased the mRNA expression levels of VEGF and ANG2 on day 2 compared to the normoxic-conditioned (NC) group. The HC group showed significant improvement in the left ventricular ejection fraction (64.4% vs 58.8% and 53.4% in the NC and control) and a greater lectin-positive area in the ischaemic region (HC:NC:control = 13:8:2). CONCLUSIONS: HC enhances the paracrine effect of a CDC sheet on angiogenesis to improve cardiac function in the chronic myocardial infarction model, which is essential for cardiomyocyte proliferation during cardiac regeneration.